Effect of Ta–TiO2 Nanoparticles in Anion Exchange Membranes: Improved Hydroxide Ion Conductivity and Mechanical Strength for Alkaline Water Electrolysis Cells - Mahmoud, Ahmed Mohamed Ahmed; Miyatake, Kenji; Tsujii, Kaito; Kakinuma, Katsuyoshi; Liu, Fanghua; Yadav, Vikrant; Xian, Fang; Guo, Lin; Wong, Chun Yik; Iwataki, Toshio; Uchida, Makoto (Macromolecular chemistry and physics, 2025)
To improve the properties of quaternized QPAF‐4 copolymers as anion exchange membranes, compositing with hydrophilic Ta–TiO2 particles are investigated. Flexible QPAF‐4/Ta–TiO2 composite membranes are obtained using solution‐casting and die coating methods. Cross‐sectional scanning electron microscopy reveals that the die coating method produces a more homogenous and uniform distribution of Ta–TiO2 particles in the composite membranes than the solution‐casting method. The Ta‐TiO2 particles promotes the suppression of water absorbability and dimensional swelling of the composite membranes which is more pronounced in the die coated membranes. The Ta–TiO2 increase hydroxide ion conductivity to 116.9 mS cm−1 at 80 °C for the die‐coated membrane, surpassing that of the pristine QPAF‐4 membrane (92 mS cm−1). Ta–TiO2 with the composite membranes survive in 4 m KOH at 80 °C for 1000 h, maintaining 96–112 mS cm−1 (88–99% remaining) of initial conductivity. All composite membranes exhibit higher mechanical robustness (elongation of >200%), with the die‐coated composite membranes. The optimized die coated composite membrane is fabricated in an alkaline water electrolysis cell achieving 1.63 V at 1.0 A cm−2 (75.5% efficiency). The effect of Ta–TiO2 nanoparticles as metal oxide fillers for anion exchange membranes is investigated. The resulting composite membranes exhibit enhanced hydroxide ion conductivity and mechanical robustness. The optimized composite membrane is applied to an alkaline water electrolysis cell with NiFeO cathode catalyst and 1 m KOH at 80 °C to achieve high performance.